Exploring barriers to using modern contraceptives and accessing safe abortion care in women who terminated unintended pregnancies in Southern Ethiopia - Mahlet A. Woldetsadik; Yeshihareg Yoseph; Mekonnen Degu (BMC Women's Health, 2024)
Abstract Background Unsafe abortion is a major medical and public health problem in Ethiopia and contributes significantly to abortion-related morbidity and mortality in the country. We explored women’s experiences with modern contraceptives and identified barriers to accessing safe abortion care and other sexual and reproductive health services. Methods We recruited participants from six health clinics and a public hospital in southern Ethiopia. We conducted one-on-one interviews with 34 women aged 18–49 years who sought abortion care within the past twelve months of the study. Interviews were recorded, transcribed verbatim, translated to English, and imported into Dedoose software. We analysed the data using a directed content analysis. Results Our findings show prevailing belief among participants that contraceptives caused infertility, abnormalities in subsequent pregnancies, and other side effects. Some of the women suggested that medical or unsafe abortions were a better alternative to using modern contraceptives for terminating unplanned pregnancies. Barriers to accessing safe abortion care included costs of services, lack of privacy, and fear of judgment from providers. Women who had negative experiences with providers were more likely to seek unsafe abortion the second time around. Conclusion Providers need to address women’s concerns about using modern contraceptives, educate their clients about the best ways to prevent unwanted pregnancies, and provide non-judgemental services. In addition, comprehensive counselling services that include contraceptive counselling should be made available to women before, during, and after abortion care. Finally, providers should strive to be facilitators of, not barriers to, safe abortion care.